Separation and purification of paraoxonase1 enzyme in women with hypothyroidism and assessment kinetic studies (The Peerian Journal, 2024)
Paraoxonases1 )PON1(, are a type of Hydrolase enzyme that have a wide range of substrates.Paraoxonase-1 is produced in the liver and then released into the bloodstream, where it binds to high-density lipoprotein (HDL) particles. Objectives :the present study aims to Purifying PON1 enzyme from fresh human blood and study kinetics represented by the study of substance concentration , pH, temperature, and time of reaction